2013
DOI: 10.1371/journal.pone.0058923
|View full text |Cite
|
Sign up to set email alerts
|

Ideal Cardiovascular Health Metrics on the Prevalence of Asymptomatic Intracranial Artery Stenosis: A Cross-Sectional Study

Abstract: Background and PurposeIntracranial Artery Stenosis (ICAS) is one of the most common causes of ischemic stroke in Asia. Previous studies have shown the number of ideal cardiovascular health (CVH) metrics was associated with lower risk of stroke. This study aimed to investigate the relationship between ideal CVH metrics and prevalence of ICAS.MethodsA random sample of 5,412 participants (selected from Kailuan Study as a reference population) aged 40 years or older (40.10% women), free of stroke, transient ischem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(44 citation statements)
references
References 42 publications
(62 reference statements)
1
43
0
Order By: Relevance
“…In adolescents, the effect of the score on aortic IMT nearly plateaued after four ideal metrics; for elasticity, a similar phenomenon was seen after three of the metrics were met [14]. However, in adults, a somewhat more linear, graded association between the ideal CVH scores with carotid IMT [13], ICAS [31], and AIP [23]. In adolescence, one does not have to reach all seven metrics to gain CVH benefits; the key is to avoid having a low ideal CVH score [14].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In adolescents, the effect of the score on aortic IMT nearly plateaued after four ideal metrics; for elasticity, a similar phenomenon was seen after three of the metrics were met [14]. However, in adults, a somewhat more linear, graded association between the ideal CVH scores with carotid IMT [13], ICAS [31], and AIP [23]. In adolescence, one does not have to reach all seven metrics to gain CVH benefits; the key is to avoid having a low ideal CVH score [14].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have accessed the relationship between CVH and AS markers [13,23,31]. Kulshreshtha A. et al confirmed that ideal CVH had a strong inverse correlation with carotid IMT, another preclinical marker for AS [13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Details and design of the study have been previously described. 19,20 From June 2010 to June 2011, a sample of 7000 participants older than 40 years was randomly selected from the Kailuan cohort using a stratified random-sampling method by age and sex based on data of the Chinese National Census from 2010. The sample size was calculated based on detection of a 7% event rate with 0.7% precision and an a value of 0.05.…”
Section: Study Populationmentioning
confidence: 99%
“…21,22 However, there has been little research on the association between the ideal CVH score and PWV, particularly from a different angle (baPWV). We therefore evaluated the association between the CVH score and baPWV among Chinese adults in a large community-based Asymptomatic Polyvascular Abnormalities in Community (APAC) Study in northern China.…”
Section: Introductionmentioning
confidence: 99%